Applied Demography and Public Health in the 21st Century - Hoque, M. Nazrul; Pecotte, Beverly; McGehee, Mary A. (Springer International Publishing : Imprint: Springer, 2017)
This book demonstrates different statistical techniques for analyzing health-related data as well as providing new techniques for forecasting and/or projecting the incidence of diseases/disorders. It presents information on a variety of health related issues from the developed and developing world. Featuring cutting edge research from distinguished applied demographers and public health specialists, the book bridges the gap between theory and research. Each chapter provides methods and materials that can be used to conduct further research aimed at promoting public health issues. This book is intended for public health professionals, health policy makers, social epidemiologists, administrators, researchers, and students in the fields of applied demography and public health who are interested in exploring the potential of ground-breaking research or who want to further develop their existing research techniques. It complements another volume in the Applied Demography Series, Applied Demography and Public Health (Springer, 2013), which describes how applied demographic techniques can be used to help address public health issues.
Keywords: Social sciences.; Public health.; Statistics.; Population.; Demography.; elektronické knihy; electronic books